2003
DOI: 10.1002/tcm.10050
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenic arrest in men with testicular hyperthermia

Abstract: Sperm is produced by a highly complex and poorly understood differentiation process known as spermatogenesis. Occupational exposure to high temperatures adversely affect testicular function, causing partial or complete spermatogenic arrest. Dyers, cooks, blast furnace workers, and men with varicocele are known to develop testicular hyperthermia, which leads to oligoasthenoteratozoospermia (OAT) and azoospermia. Semen analysis of 122 infertile men (and 25 fertile controls), following the WHO guidelines, 1999, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 25 publications
0
31
1
1
Order By: Relevance
“…Undescended testes exposed to a high temperature are likely to complete spermatogenic failure in that decreases in sperm count and motility are developed [25,26,27], albeit testicular volume is not affected [28]. Early orchidopexy is proposed to prevent morphological changes in undescended testes and can improve fertile outcome [3,24,29].…”
Section: Discussionmentioning
confidence: 99%
“…Undescended testes exposed to a high temperature are likely to complete spermatogenic failure in that decreases in sperm count and motility are developed [25,26,27], albeit testicular volume is not affected [28]. Early orchidopexy is proposed to prevent morphological changes in undescended testes and can improve fertile outcome [3,24,29].…”
Section: Discussionmentioning
confidence: 99%
“…Testicular hyperthermia has been known to have a deleterious effect on male fertility since the time of Hippocrates and is a well-recognized cause of impaired sperm production (1). Its detrimental effect has been demonstrated in both animal models and in humans (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…If semen sample contains 4% of morphologically normal forms, it is considered fit. It is observed in this study that twenty one (21) persons in all age groups have shown morphologically abnormal sperm. In the case of semen morphology, there is a report of Teratozoospermia in 72% of heavy alcoholic persons and 63% moderate alcoholic persons [39].…”
Section: Discussionmentioning
confidence: 53%
“…Spermatogenesis is sensitive to a variety of chemical and physical stressors. Testicular hyperthermia is one such cause which has deleterious effect on male fertility since the time of Hippocrates and is a well-recognized cause of impaired sperm production [21]. In all the persons who consumed alcohol, semen color was found to be white in color.…”
Section: Discussionmentioning
confidence: 99%